GNSS assessment of sentinel-3A ECMWF tropospheric delays over inland waters. Issue 12 (15th December 2020) - Pearson, Christopher; Moore, Philip; Edwards, Stuart
Abstract: Over land and inland waters satellite radar altimetry is being used in numerous applications including polar mass change, ice topography, river and lake heights and soil moisture. To achieve high accuracy altimetric range measurements, geophysical corrections are applied including the Zenith Total Delay (ZTD) which varies spatially, temporally and with altitude. Over oceans, the wet tropospheric component of the ZTD is usually derived from onboard radiometers. However, over land, the radiometer return is saturated and the zenith wet and dry tropospheric delays are derived separately as output of a meteorological model such as that processed by the European Centre for Medium-Range Weather Forecasts (ECMWF). Using Global Navigation Satellite System (GNSS) stations located near Sentinel-3A ground tracks and correcting for any height difference the ECMWF model is compared to the ZTD estimated from GNSS data, quantifying the likely error for inland water and land applications. We found that, globally, there is a median bias of −3 mm between the ECMWF model and GNSS values with median absolute deviation (MAD) of 7.3 mm but with clear spatial and temporal variations. Spatially, ZTD differences are greatest within the tropics with MAD values exceeding 11 mm, over double that of points within the Arctic Circle (<5 mm). Temporally, the ECMWF model differs from GNSS values more during summer months. Northern Hemisphere summer (June–August) has an approximately 60% larger MAD than December-February with the summer MAD approximately 20% smaller in the Southern Hemisphere. Assessment of the tropospheric error is quantified for the largest river catchments for application to inland water heights. The close proximity of altimetric data, GNSS receiver and inland water gauges on the Amazon and Orange rivers and Lake Ontario confirms the preference for GNSS derived ZTD. Overall, the altimetric community can be reassured that the tropospheric contribution to the error budget for inland water applications is less generally than 20 mm at 1 σ in all major catchments.